Supporting friends and family of adults with a primary brain tumour: A systematic review. (11th October 2021) - Heinsch, Milena; Cootes, Hannah; Wells, Hannah; Tickner, Campbell; Wilson, Jessica; Sultani, Grace; Kay‐Lambkin, Frances
Abstract: Expanding on the limited work in supportive care for friends and family caregivers of adults with a primary brain tumour, this review sought to examine all available evidence since 2010 on the efficacy and feasibility of supportive interventions for this population including non‐controlled studies. A systematic review of the literature was conducted on the feasibility and effectiveness/efficacy of supportive interventions for brain cancer caregivers in line with PRISMA guidelines. 13 studies met the eligibility criteria and were identified for inclusion. Most interventions employed tailored psychoeducation, and expert involvement via psychotherapy or care coordination. Only two interventions demonstrated clinically significant improvements. Findings indicate that dyadic yoga programs, and programs that enhance caregiver mastery to manage patient behavioural problems, may lead to improvements in some clinical outcomes. Results highlight the diverse nature of supportive interventions and indicate that support for primary brain tumour caregivers is currently suboptimal. Our findings illustrate an overall low certainty of evidence, with a need for more adequately powered randomised controlled trials. As the complexities of brain cancer care‐giving are an obstacle to standardised interventions, this review underscores the need for future trials to incorporate complimentary qualitative research methodologies.